Technical-economical evaluation of pavement recycling alternatives - Pereira, Paulo A. A. (2006)
Pavement recycling is becoming an increasingly important alternative worldwide for maintenance of highways, once sustainability and environmental issues have continued to receive more attention. The reference point is that of considering the use of road materials in a closed cycle, in which a natural material, previously used in road construction, should not be rejected in the following life-cycle. The objective of this paper is that of analysing flexible pavement recycling alternatives techniques, including reclaimed material from flexible pavements recycled with emulsion, cement and reused in a hot-mix. Based on the results obtained from field and laboratory tests (stiffness modulus, resistance to fatigue and permanent deformation), carried out using different materials, a set of numerical simulations were made for the design of pavement structures where those mixtures would be used, according to their characteristics and traffic specifications. The results of pavement design were obtained using the linear elastic theory in the BISAR program. With the results obtained from the pavement design, the cost savings of using recycled materials in the different pavement structures were quantified and compared to a standard option, where new natural aggregates and binders would be used. In this analysis, the consideration of the reduction in the disposal of reclaimed pavement materials was also addressed. The results of this research will support the production of specifications, thus facilitating a more accurate reuse of natural resources, assisting in the protection of the environment, as well as in a more effective use of financial resources available for the activity of pavement maintenance and rehabilitation.